On the puzzling distribution of cholesterol in the plasma membrane. (September 2016) - Giang, H.; Schick, M.
Abstract : Highlights: Cholesterol was expected to be mostly in the outer leaflet of the plasma membrane. Cholesterol is not found to be mostly in the outer leaflet. We propose it is drawn to the inner leaflet by phosphatidylethanolamine (PE). Cholesterol relieves the bending energy due to the PE in the inner leaflet. Cholesterol dilutes the PE and also reduces its spontaneous curvature. Abstract: The distribution of cholesterol between the two leaves of the plasma membrane in mammalian cells presents a conundrum; given cholesterol's known affinity for sphingomyelin, which resides predominantly in the exoplasmic leaf, why is it that experiment finds a majority of the cholesterol in the cytoplasmic leaf? This article reviews a recently proposed solution to this puzzle.